Religion and ethnicity among Muslims - Saiyed, A. R. 1931-1989.; Saiyed, V. V.; Talib, Mohammad (Jaipur : Rawat Publications, 1995)
In Indian context.
Includes bibliographical references and index.
Keywords: ISLAM -- INDIA; ETHNICITY -- INDIA; MUSLIMS -- INDIA -- SOCIAL CONDITIONS; INDIA -- SOCIAL CONDITIONS